Análisis de infraestructura social en colombia (2021)
Colombia, like many developing countries, has focused on promoting the growth of road and productive infrastructure, leaving aside social infrastructure, which can be defined as physical assets of operation that serve as social services, among these are facilities such as schools, universities, hospitals, clinics, and prisons. In order to establish a panorama of social infrastructure in Colombia, a sample of bids was studied over a period of 5 years to determine how the contracting processes were developed. Bibliographic sources were reviewed to determine what social infrastructure is, then the pages of the Electronic System for Public Contracting (SECOP) in Colombia were studied. This study found a total of 404 projects, of which 76.49% are related to improvement projects for educational entities, 21.78% are related to improvement projects for clinics or hospitals and 1.73% are related to prisons. Likewise, the need to improve social infrastructure is determined, and even more so in prison development projects.